Unveiling the gaps: A comprehensive, equity-focused observational examination of Emergency Department discharge - Lynn G. Jiang; Maree Sats; Sowmya Sanapala; Madeleine Tierney; Brady Rippon; Natalie C. Benda; Radhika Sundararajan; Peter A.D. Steel (PLoS ONE, 2025)
Objectives Prior work has shown that Emergency Department (ED) discharge instructions are often incomplete and poorly comprehended , leading to adverse events. Given the critical importance of effectively communicating ED discharge instructions, we performed a comprehensive evaluation of current adult ED discharge practices at two hospitals compared to a conceptual composite gold standard. Methods This prospective observational study was conducted at two large academic urban EDs. ED patients were purposively selected for observation to ensure diverse representation including non-English language preferring (NELP) patients. Research Assistants (RAs) observed all provider-patient interactions throughout the patient’s ED encounter, documenting all discharge-related discussions. Verbal discharge and discharge documentation content were compared to a conceptual “gold-standard” checklist developed from consensus national guidelines. Results Between September 2023 to March 2024, a total of 175 adult patient ED courses were observed. The majority of verbal communication regarding ED discharge included ED diagnosis (87%), ED diagnostic results (87%), medications (81%) and follow-up plan (78%). Only half (54%) included ED return precautions. Discharge documentation content mirrored these findings, except for ED diagnostic results (69%) and ED return precautions (81%). Assessment of comprehension occurred during only 53% of discharges, with 46% of patients having the opportunity to ask follow-up questions. For NELP patients, 12% of verbal discharges and 55% of discharge documentation were not in the patients’ preferred language. Conclusion Much of the recommended ED discharge content was provided to the patient. Divergent content gaps identified across verbal discharge and discharge documentation support the pragmatic value of bimodal discharge processes. Given the demonstrated impact of discharge instruction comprehension on improving patient adherence, important foci for future process improvement includes assessing patient comprehension and exploring feasible solutions to facilitate the use of preferred language discharge documentation instructions.